ECONOMIC FACTORS OF THE ENEOLITHIC PERIOD IN THE SOUTHERN ARAL REGION AND THE LOWER ZARAFSHAN VALLEY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article highlights the socio-economic development factors of Eneolithic society in the Southern Aral region and the Lower Zarafshan Valley.